2017
DOI: 10.1371/journal.ppat.1006568
|View full text |Cite
|
Sign up to set email alerts
|

Ligation of Dectin-2 with a novel microbial ligand promotes adjuvant activity for vaccination

Abstract: The development of vaccines against fungi and other intracellular microbes is impeded in part by a lack of suitable adjuvants. While most current vaccines against infectious diseases preferentially induce production of antibodies, cellular immunity is essential for the resolution of fungal infections. Microbes such as fungi and Mycobacterium tuberculosis require Th17 and Th1 cells for resistance, and engage the C-type lectin receptors including Dectin-2. Herein, we discovered a novel Dectin-2 ligand, the glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The mutation frequency of PRA1 produced by CRISPR/Cas9 editing was much higher than the approximately 0.05 to 2% typical of traditional homologous-recombination-based gene editing in Blastomyces (for example, see reference 7 ). We sought to determine whether this high targeting efficiency was locus specific, so we designed sgRNA vectors to target several other Blastomyces genes, including (i) the high-affinity zinc transporter ZRT1 , (ii) the recently identified dectin-2 ligand Blastomyces endoglucanase 2 ( BL-ENG2 ) ( 10 ), and (iii) an exogenously introduced mCherry gene in an engineered Blastomyces strain ( 11 ). For these attempts, we chose multiple sgRNA sequences for each target.…”
Section: Resultsmentioning
confidence: 99%
“…The mutation frequency of PRA1 produced by CRISPR/Cas9 editing was much higher than the approximately 0.05 to 2% typical of traditional homologous-recombination-based gene editing in Blastomyces (for example, see reference 7 ). We sought to determine whether this high targeting efficiency was locus specific, so we designed sgRNA vectors to target several other Blastomyces genes, including (i) the high-affinity zinc transporter ZRT1 , (ii) the recently identified dectin-2 ligand Blastomyces endoglucanase 2 ( BL-ENG2 ) ( 10 ), and (iii) an exogenously introduced mCherry gene in an engineered Blastomyces strain ( 11 ). For these attempts, we chose multiple sgRNA sequences for each target.…”
Section: Resultsmentioning
confidence: 99%
“…Mannose receptor recognizes mannose and other sugar moieties on the surface of microbial cells . The CLR dectin‐2 has previously been shown to respond to mannan stimulation, and recent work has also identified the glycoprotein Bl‐Eng2 of Blasotmyces dermatitidis as a bona‐fide ligand for this receptor . A newly defined CLR, MelLec enables the host to sense melanin on pathogens including Aspergillus spores .…”
Section: Fungal Recognition and T‐cell Priming The Lungmentioning
confidence: 99%
“…For instance, Mincle recognizes SAP30, a protein released by dead cells (33). Moreover, we observed that digestion of the crude, water-soluble, cell wall extract (CWE) from Blastomyces vaccine yeast with either proteinase K or endo-mannosidases reduced Dectin-2 recognition as measured by reduced ligand activity by corresponding reporter cells (23), suggesting that both the protein and glycan moieties may contribute.…”
Section: Dectin-2 Recognizes Mannose Residues In Bl-eng2 But Not Thementioning
confidence: 96%
“…4C-F). As a positive control for CD4 + T cell priming, we vaccinated mice with full length Bl-Eng2 since it harbors both the antigen and adjuvant properties (23,34).…”
Section: Dectin-2 Senses Bl-eng2's C-terminal O-linked Glycans But Nmentioning
confidence: 99%